THE RELATIONSHIP PREEKLAMSIA WITH GRAVIDA FOR PREGNANT WOMEN IN THE DELIVERY ROOM RSIA MUHAMMADIYAH PROBOLINGGO - Malayanti Umami; Tutik Ekasari; Mega Silvian Natalia (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Preeclampsia is a disorder found during pregnancy with signs such as hypertension, proteinuria, and edema which usually occurs after 20 weeks to 48 hours of gestation which is the biggest cause of death in pregnant women besides infection and bleeding. The incidence of pre-eclampsia can be obtained from the history of the pregnant woman's pregnancy.The purpose of this study was to determine whether there is a relationship between gravida and the incidence of preeclampsia in pregnant women in the maternity ward of RSIA Muhammadiyah Probolinggo. The research method used is an analytic correlation study with a cross sectional approach using secondary data through medical records. The samples used were all pregnant women who experienced pre-eclampsia in the period January 1, 2021 – December 31, 2021.The sampling technique used was simple random sampling with a total of 100 pregnant women. Analysis using Spearman rank with SPSS 2.0.The results of this study showed that 47% of primigravida mothers had severe preeclampsia and 15% had mild preeclampsia. While in multigravida as much as 30% had mild preeclampsia and 8% had severe preeclampsia. The results of the SPSS calculation using Spearman Rank with a sample size of 100, then the value of Sig. (2-tailed) is 0.00 as the basis for the decision above, it can be concluded that there is a significant relationship between Gravida and the incidence of Pre-eclampsia. Then from the output above, it is known that the Correlation Coefficient value is 0.534, so this value indicates a relationship with a moderate correlation between Gravida and the level of Pre-eclampsia.This is due to blocking antibodies against placental antigens formed in the first pregnancy to cause preeclampsia. This theory also states that due to a decrease in human antigen G protein (HLA), which plays an important role in modulating the immune response, the mother rejects the products of conception.